A general and efficient synthesis of 5, 6-dihydrodibenzo[b, h][1, 6]naphthyridine derivatives. Issue 49 (7th December 2016) - Dobrowolski, Jeremy C.; Katen, Alice; Fraser, Benjamin H.; Bhadbhade, Mohan; Black, David StC.; Kumar, Naresh
Graphical abstract: Highlights: Nitrogen heterocycles related to the anti-malarial natural product dependensin. An efficient two-step synthesis of 5, 6-dihydrodibenzo[ b, h ][1, 6]naphthyridines. Synthesis of 13 novel 6, 7-diphenyl-5, 6-dihydrodibenzonaphthyridine derivatives. Benzonaphthyridine fluorescence emission maximum is dependent on solvent polarity. Abstract: A two-step procedure for the synthesis of dihydrodibenzonaphthyridine derivatives from benzaldehydes and 2-aminoacetophenones, proceeding through a substituted dihydroquinolone intermediate, is described. The synthetic protocol allows for a versatile and robust coupling method between a range of 2-aminoacetophenones or 2-aminobenzophenones and a selection of substituted dihydroquinolones.